Flavonoids : future pharmaceutical agents. - Ahmed, Qamar Uddin (IIUM Press, 2011)
Flavonoids have become very popular owing to their many health promoting effects. They are polyphenolic compounds, occur naturally and are widely distributed in plant kingdom performing many core functions including defense from attack by insects and microorganisms. These polyphenolic compounds are plant-derived secondary metabolites with interesting biological properties. Several in vivo and in vitro experiments have evidently and explicitly shown that they could be potential pharmaceutical agents in the treatment of many human diseases, including cognitive impairments, cardiovascular disease, diabetes, and cancer